Measurements of quarkonia production - Massacrier Laure (EPJ Web of Conferences)
Quarkonium production in high-energy hadronic collisions is a useful tool to investigate fundamental aspects of Quantum Chromodynamics, from the proton and nucleus structure to deconfinement and the properties of the Quark Gluon Plasma (QGP). In these proceedings, emphasis is made on few recent quarkonium results from the RHIC and LHC colliders in proton-proton (pp), proton-nucleus (p-A) and nucleus-nucleus (A-A) collisions. In addition, results for some key observables are compiled to discuss the state-of-the-art in quarkonium production, with a focus on quarkonium hadroproduction.